Free Flap Reconstruction after Complications of Total Ankle Arthroplasty: Case Series and Review of the Literature - Lu, Jocelyn; Elmarsafi, Tammer; Steinberg, John S.; Kim, Paul J.; Attinger, Christopher E.; Cooper, Paul; Evans, Karen K. (Journal of Reconstructive Microsurgery Open, 2018)
Background Postoperative complications of total ankle arthroplasty (TAA) include anterior surgical site dehiscence, hardware failure, infection, and amputation. Early intervention with free flap may provide TAA salvage. We report the largest series of failed TAA require microsurgical free tissue transfer, identify risk factors, and examine the long-term post-free flap outcomes.Materials and Methods This is a case series of consecutive patients from a single institution dedicated to limb salvage. Inclusion criteria included patients who underwent TAA with complications related to the index surgery and underwent microsurgical free tissue transfer. Nine patients were identified within the inclusion parameters.Results Patients presented with osteomyelitis 4 (44%), soft tissue infections 4 (44%), and wound dehiscence 1 (11%) following TAA. Three (33%) radial forearm free flaps and six (67%) anterolateral thigh flaps were used, with a 100% microsurgical success rate. Preoperative angiography revealed six (67%) patients with anterior tibial artery occlusion at the level of the ankle or below. Patients required an average of 2.7 ± 1 (range 1–4) operative débridements prior to free flap, with successful flap outcome and return to full weight bearing status in nine (100%) patients. The mean long-term lower extremity functional scale score was 62 out of 80 points.Conclusion Microsurgical free tissue transfer is an effective and favorable strategy to attain a stable soft tissue envelope for patients presenting with surgical site complications following TAA. We recommend early involvement with plastic surgery and endovascular angiography to evaluate the integrity of the anterior tibial artery.
Keywords: microsurgical free flap; total ankle arthroplasty; limb salvage